Ways to reduce influence of air components on health of aic workers - Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович (НУБіП України, 2021)
EN : Production and processing of agricultural products, repair of machinery in the agro-industrial complex associated with the use of various machinery and equipment. Sometimes in production conditions are created when the worker is affected by the nature and degree of influence of harmful production factors.
Keywords: тhe ecological situation; agro-industrial complex; нygienic standards; permissible parameters; carbon dioxide; intoxication; nitrogen; oxygen